Strategic Leadership as a Strategy Implementation Driver and Its Effect on the Competitive Advantage of Commercial Banks in Kenya - Kerama, Peninah Kerubo; King’oina, Peter; Maengwe, James (Integrasi Sains Media, 2025)
This study examines the effect of strategic leadership as a strategy implementation driver on the competitive advantage of tier-three commercial banks in Kenya. Despite their numerical dominance, these banks continue to record declining market shares compared to larger and more established competitors, raising concerns about the effectiveness of their strategy implementation mechanisms. Anchored on Porter’s Theory of Competitive Advantage and the Contingency Theory of Leadership, the study adopted a cross-sectional survey design targeting 719 management employees across 22 tier-three banks. Using stratified random sampling, 172 participants were selected, and data were collected through a structured questionnaire. Descriptive and inferential analyses were conducted using SPSS. The regression results indicated that strategic leadership had a statistically significant positive effect on competitive advantage (β = 0.426, p < 0.05), explaining 38.4% of the variation in competitiveness among the banks. The findings underscore that ineffective strategic leadership practices—particularly lack of clear strategic direction, limited leadership by example, and weak employee alignment—contribute to the declining competitiveness of tier-three banks. The study contributes to strategic management literature by empirically validating leadership as a key driver of strategy implementation effectiveness in emerging market banking contexts. It recommends that bank executives institutionalize strategic leadership practices to foster organizational alignment, adaptability, and sustainable competitive advantage.